Field‐scale Variation in Colloid Dispersibility and Transport: Multiple Linear Regressions to Soil Physico‐Chemical and Structural Properties. Issue 5 (1st September 2014) - Norgaard, Trine; Moldrup, P.; Ferré, T. P. A.; Katuwal, S.; Olsen, P.; de Jonge, L. W.
Abstract : Water‐dispersible soil colloids (WDC) act as carriers for sorbing chemicals in macroporous soils and hence constitute a significant risk for the aquatic environment. The prediction of WDC readily available for facilitated chemical transport is an unsolved challenge. This study identifies key parameters and predictive indicators for assessing field‐scale variation of WDC. Samples representing three measurement scales (1‐ to 2‐mm aggregates, intact 100‐cm 3 rings, and intact 6283 cm 3 columns) were retrieved from the topsoil of a 1.69‐ha agricultural field in a 15‐m by 15‐m grid to determine colloid dispersibility, mobilization, and transport. The amount of WDC was determined using (i) a laser diffraction method on 1‐ to 2‐mm aggregates and (ii) an end‐over‐end shaking method on 100‐cm 3 intact rings. The accumulated amount of colloids leached from 20‐cm by 20‐cm intact columns was determined as a measure of the integrated colloid mobilization and transport. The WDC and the accumulated colloid transport were higher in samples from the northern part of the field. Using multiple linear regression (MLR) analyses, WDC or amount of colloids transported were predicted at the three measurement scales from 24 measured, geo‐referenced parameters to identify parameters that could serve as indicator parameters for screening for colloid dispersibility, mobilization, and transport. The MLR analyses were performed at each sample scale using all, only northern, and only southern field locations. Generally, the predictive power of the regression models was best on the smallest 1‐ to 2‐mm aggregate scale. Overall, our results suggest that different drivers controlled colloid dispersibility and transport at the three measurement scales and in the two subareas of the field.